Polycyclic aromatic hydrocarbons from wood pyrolyis in charcoal production furnaces - Barbosa, JMD; Re-Poppi, N.; Santiago-Silva, M. (Elsevier B.V., 2006)
Polycyclic aromatic hydrocarbons (PAH) were measured in smoke samples from wood carbonization during charcoal production, in both particulate matter (PM) and gaseous phases. Samples were acquired using a medium-volume air sampler at 1.5 m distance from the furnace. Particle-bound PAH were collected on Fluoropore polytetrafluoroethylene filters and gas-phase PAH were collected into sorbent tubes with XAD-2 resin. PAH were extracted with dichloromethane-methanol and analyzed using gas chromatography-mass spectrometry. The results showed total emission from the furnace of 26 mu g/m(3) for the 16 PAH and 2.8 mu g/m(3) for the 10 genotoxic PAH (from fluoranthene to benzo[g,h,i]perylene). High emission of 16 PAH in the first 8 h of wood carbonization was detected (64 mu g/m(3); 56% of the total emission). Associated with PM, 11% of the total emission of 16 PAH (in both phases) and 60% of 10 genotoxic PAH were found. Relative ratios (for example, [Phe]/[Phe] + [Ant]) for the PAH of the same molecular weight were obtained and compared with the published data. The concentrations of benzo[a]pyrene equivalent (BaPeq) were estimated using the list of toxic equivalent factors suggested by Nisbet and LaGoy, 1992. The values of 0.30 and 0.06 mg/m3 were obtained for the total concentrations of BaPeq in PM and gaseous phase, respectively. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: charcoal; PAH; gas-particle distribution; toxic equivalency factors